2018
DOI: 10.1016/j.electacta.2018.05.058
|View full text |Cite
|
Sign up to set email alerts
|

A detailed look into hydrogen electrochemical oxidation on ceria anodes

Abstract: Using the Nernst-Planck-Poisson model and a detailed reaction mechanism, we studied the hydrogen electrochemical oxidation on a ceria anode. Resistances caused by surface kinetics, and bulk transport of oxide-ion vacancies and electrons are computed individually to identify the dominant resistive process. The effect of operating conditions like temperature and gas-phase composition on the polarization resistance is evaluated and compared with the experimental data obtained by Electrochemical Impedance Spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(42 reference statements)
1
7
0
Order By: Relevance
“…Correspondingly, OH • o and S x o are hydroxyl, and sulfur ions residing at anionic sites, respectively. In line with the previous findings [36,37], reaction (2) is the rate-determining step. The above scheme exhibits a global interaction of sulfur with ceria with an assumption that OH • o and S x o do not diffuse into the bulk.…”
Section: Elementary Kinetic Modeling Of Ceria Cellsupporting
confidence: 91%
See 3 more Smart Citations
“…Correspondingly, OH • o and S x o are hydroxyl, and sulfur ions residing at anionic sites, respectively. In line with the previous findings [36,37], reaction (2) is the rate-determining step. The above scheme exhibits a global interaction of sulfur with ceria with an assumption that OH • o and S x o do not diffuse into the bulk.…”
Section: Elementary Kinetic Modeling Of Ceria Cellsupporting
confidence: 91%
“…We find that a rise in polarization resistance occurs primarily at low frequencies, even for pattern electrode cells, which is consistent with our previous findings. In our previous studies [36,37], where the model was developed for hydrogen oxidation on ceria, the low-frequency process was attributed to the electrochemical process, including adsorption, charge transfer, and desorption. Even if sulfur does not participate in the charge transfer process, it is possible to link an increase in polarization resistance to the adsorption of sulfur species on ceria even if sulfur does not participate in charge transfer.…”
Section: Discussion On H 2 S Poisoning Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the aim is to formulate a simplified surface reaction overpotential accounting for the rate limiting step. Tabish et al 56 summarized the different rate-determining steps for ceria electrodes reported in the literature and concluded that the majority of the studies depict a charge transfer step to be the rate-determining step, though there are differences in the understanding of how and where this rate limiting charge transfer process takes place. We therefore use the following formulation for the surface reaction overpotential Z SR , which implies that the charge transfer is the ratedetermining step and that all other intermediate steps are very close to the equilibrium.…”
Section: Application Of the Model For Cgo10mentioning
confidence: 99%